Perawatan ulang saluran akar gigi molar kanan mandibula - Steward; Stefani, Rosita (Jurnal Kedokteran Gigi Terpadu, 2024)
Background: An inadequate root canal treatment allows bacteria to thrive and survive, which is a major cause of endodontic failure. An appropriate treatment plan can be determined after a precise and accurate diagnosis has been made. Objective: The purpose of this case report is to demonstrate the root canal retreatment on a posterior mandibular tooth with periapical lesions. Case report: A 37-year-old female patient came with complaints of discomfort when chewing food with her lower right back tooth. The tooth had been treated ten years ago with a metal filling, which was replaced with a tooth-colored filling a year ago. Intra-oral examination of tooth 46 showed composite resin restoration on the distobuccal surface. Radiographic findings showed that there was restoration on the distal surface that reaches the floor of the pulp chamber and radiolucency in the furcation area. Root canal retreatment was performed based on the diagnosis of acute apical periodontitis et causa necrotic pulp. The treatment plan involved root canal retreatment with direct resin composite restoration. Root canal retreatment starts with the application of a rubber dam, followed by the removal of any existing restoration and caries, opening the cavity, root canal exploration, and root canal shaping. Biomechanical preparation was carried out with Protaper Hand Use with crown down technique, in conjunction with 2,5% NaOCl irrigation. The initial visit concludes with the disinfection of the root canal with calcium hydroxide. The following treatment involved a subjective and objective assessment, removal of the temporary filling, cleaning of calcium hydroxide, and final irrigation with 2,5% NaOCl, 17% EDTA, and 2% CHX. Obturation was accomplished utilizing the vertical condensation technique. The restoration was completed with composite resin. Conclusion: Root canal retreatment on teeth with acute apical periodontitis et causa necrotic pulp was successfully carried out.